Impact of Male Hypogonadism on Bone Mineral Density in Childhood Hemato-Oncologic Disease - Kim, Sungeun (J Endocr Soc, 2021)
Introduction: Patients with childhood hemato-oncologic diseases have many medical problems, not only due to disease itself, but also adverse effects of specific treatment that patients had. Osteoporosis, one of the most common side effects of the treatment, decreases quality of life when the disease progresses. Our study investigated the impact of male hypogonadism on secondary osteoporosis in childhood hemato-oncologic patients, using association between male sex hormone and bone mineral density (BMD) measured by dual energy X-ray absorptiometry (DXA). Methods: This study collected BMD score (T-score) of 52 male subjects who were diagnosed with hemato-oncologic diseases in the past (average age of 22.3 years at DXA examination). All subjects measured serum testosterone and we divided them into two subgroups according to gonadal status. The first group, called hypogondal group, was a group of subjects with serum testosterone level less than 3.5 ng/ml. The other group was classified into eugonadal group, with serum testosterone level equal or more than 3.5 ng/ml. Mean BMD score of spine and hip were presented and compared between the two groups. Furthermore, relativity with other risk factors for osteoporosis was calculated using multiple regression analysis. Results: Overall, spine BMD in the hypogondal group did not significantly differ from the eugonadal group. However, hip BMD was significantly lower in the hypogonadal group (mean difference; 0.8, p = 0.023). Furthermore, testosterone level itself showed linear correlation with BMD score in hip (p = 0.013). When other risk factors for osteoporosis were taken into account, hemato-oncologic patients treated with total body irradiation also had significantly lower hip BMD (p = 0.007) compared with non-irradiation group. Hypogonadism still remained a significant factor for decreased bone mineral density in hip (p = 0.022). Conclusions: Hemato-oncologic patients with hypogonadism or previously treated with total body irradiation are at increased risk of decreased bone mineral density in both hips. Hypogonadism alone remains independent risk factor for osteoporosis in hip. Attention of these male patient should be paid to prevent the incidence of secondary osteoporosis.